NF막을 이용한 EDCs, PhACs, PCPs 물질의 제거 특성 평가 - 장혜원; 박찬혁; 홍승관; 윤여민; 정진영; 정윤철 (대한상하수도학회, 2007)
Reports of endocrine disrupting compounds (EDCs), pharmaceutically active compounds (PhACs), and personal care products (PCPs) have raised substantial concern in important potable drinking water quality issues. Our study investigates the removal of EDCs, PhACs, and PCPs of 10 compounds having different physico-chemical properties (e.g., molecular weight, and octanol-water partition coefficient (Kow)) by nanofiltration (NF) membranes. The rejection of micropollutants by NF membranes ranged from 93.9% to 99.9% depending on solute characteristics. A batch adsorption experiments indicated that adsorption is an important mechanism for transport/removal of relatively hydrophobic compounds, and is related to the octanol-water partition coefficient values. The transport phenomenon associated with adsorption may also depend on solution water chemistry such as pH and ionic strength influencing the pKa value of compounds. In addition, it was visually seen that the retention was somewhat higher for the larger compounds based on their molecular weight. These results suggest that the NF membrane retains many organic compounds due to both hydrophobic adsorption and size exclusion mechanisms.